Spatiotemporal expression patterns of Pax6 in the brain of embryonic, newborn, and adult mice - Duan, D.; Fu, Y.; Paxinos, G.; Watson, Charles (Springer, 2012)
The transcription factor Pax6 has been reported to specify neural progenitor cell fates during development and maintain neuronal commitments in the adult. The spatiotemporal patterns of Pax6 expression were examined in sagittal and horizontal sections of the embryonic, postnatal, and adult brains using immunohistochemistry and double immunolabeling. The proportion of Pax6-immunopositive cells in various parts of the adult brain was estimated using the isotropic fractionator methodology. It was shown that at embryonic day 11 (E11) Pax6 was robustly expressed in the proliferative neuroepithelia of the ventricular zone in the forebrain and hindbrain, and in the floor and the mesencephalic reticular formation (mRt) in the midbrain. At E12, its expression emerged in the nucleus of the lateral lemniscus in the rhombencephalon and disappeared from the floor of the midbrain. As neurodevelopment proceeds, the expression pattern of Pax6 changes from the mitotic germinal zone in the ventricular zone to become extensively distributed in cell groups in the forebrain and hindbrain, and the expression persisted in the mRt. The majority of Pax6-positive cell groups were maintained until adult life, but the intensity of Pax6 expression became much weaker. Pax6 expression was maintained in the mitotic subventricular zone in the adult brain, but not in the germinal region dentate gyrus in the adult hippocampus.There was no obvious colocalization of Pax6 and NeuN during embryonic development, suggesting Pax6 is found primarily in developing progenitor cells. In the adult brain, however, Pax6 maintains neuronal features of some subtypes of neurons, as indicated by 97.1% of Pax6-positive cells co-expressing NeuN in the cerebellum, 40.7% in the olfactory bulb, 38.3% in the cerebrum, and 73.9% in the remaining brain except the hippocampus. Differentiated tyrosine hydroxylase (TH) neurons were observed in the floor of the E11 midbrain where Pax6 was also expressed, but no obvious colocaliztion of TH and Pax6 was detected. No Pax6 expression was observed in TH-expressing areas in the midbrain at E12, E14, and postnatal day 1. These results support the notion that Pax6 plays pivotal roles in specifying neural progenitor cell commitments and maintaining certain mature neuronal fates.